SOME ASPECTS OF TEETH ERUPTION. A LITERATURE REVIEW - L.V. Smaglyuk; Н.V. Voronkova; A.Y. Karasiunok (Проблеми екології та медицини)
In modern dental practice, one of the complaints of patients is unsatisfactory appearance due to the visually disproportionate size of teeth. Diagnostic assessment of the smile reflects the amount of gum and tooth tissue exposed. This emphasizes the growing need for the exchange of information and scientific knowledge between orthodontists and periodontists, an integrated approach to the treatment of orthodontic patients. The position of the gums is clinicalу important because it is not static. Tooth eruption involves a complex of stages that have not yet been widely studied. According to the concept of continuous eruption, it does not stop, even when the teeth are in contact with their functional antagonists, but lasts a lifetime. The normal state of passive eruption should lead to the location of the cement-enamel joint (CEJ) approximately in the area of the base of the furrow and 2 mm from the ridge of the alveolar bone. The active eruption is the movement of teeth towards the occlusal plane, whereas the passive eruption is the exposure of teeth by apical migration of the gums. The passive eruption usually occurs after teething and continues in adolescents and finally stops after facial growth. Altered passive eruption (APE) (also known as delayed passive eruption) occurs when the edge of the gums is incorrectly (occlusively) located on the anatomical crown in adulthood and does not approach the CEJ. The "normal" position of the gingival margin to the CEJ is usually considered to be on or near the CEJ in the fully incised teeth of adults. The prevalence of APE in the adult population is currently poorly studied, possibly due to the lack of clear diagnostic criteria. Thus, Volchansky and Cleaton-Jones, based on a survey of 1,025 patients aged 24.2±6.2 years, recorded 12.1% of cases of APE. The analysis of the literature did not reveal any reliable etiological factors that cause the impossibility of the tooth eruption and cause such morphology of the CEJ. The greatest clinical significance of APE is its aesthetic consequences. As a rule, this is a change in dentofacial harmony, which is manifested in the following: the square appearance of the crowns, the exposure of the gums during a smile, smoothed gingival scallops. An integrated approach to the treatment of patients with APE includes consideration of periodontal interventions, restorative manipulations, and orthodontic treatment. Thus, the altered passive eruption is an unusual physiological variation in the morphology of the dental-gum complex, which leads to aesthetic disorders and is considered a risk factor for periodontal disease. Therefore, it is necessary to pay attention to the presence of altered teeth eruption when planning the orthodontic treatment. Correction of malocclusions should be integrative.